2019
DOI: 10.1001/jamaneurol.2019.1534
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Cerebrospinal Fluid Neurofilament Light Protein in Neurology

Abstract: Objectives To assess to what extent educational differences in total life expectancy (TLE) and disability-free life expectancy (DFLE) could be reduced by improving fruit and vegetable consumption in ten European countries. Methods Data from national census or registries with mortality follow-up, EU-SILC, and ESS were used in two scenarios to calculate the impact: the upward levelling scenario (exposure in low educated equals exposure in high educated) and the elimination scenario (no exposure in both groups). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
433
8
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 563 publications
(483 citation statements)
references
References 140 publications
32
433
8
10
Order By: Relevance
“…Our findings provide insights into why NEFL is a promising biomarker for AD dementia and its progression as shown by studies of CSF and plasma NEFL in AD 49,50,54,55 .…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Our findings provide insights into why NEFL is a promising biomarker for AD dementia and its progression as shown by studies of CSF and plasma NEFL in AD 49,50,54,55 .…”
Section: Discussionmentioning
confidence: 68%
“…Among the 23 proteins associated with both cognitive diagnosis and cerebral atherosclerosis independently of the other 8 measured pathologies, NEFL and NEFM were noteworthy since prior work has shown that their CSF levels associated with AD (Table 1B) [48][49][50] . In light of these findings, we examined whether NEFL and NEFM were associated with cerebral atherosclerosis specifically or with other measured pathologies as well.…”
Section: Nefl and Nefm Proteins Are Associated With Cerebral Atheroscmentioning
confidence: 98%
“…The 68 kDa neurofilament light chain (NfL) is essential for the assembly of the complex as it forms its backbone and is released into extracellular fluids in response to axonal damage. 6,7 Several studies have shown elevated levels of NfL in the CSF of patients suffering from neurodegenerative conditions. [7][8][9] Further, CSF NfL levels seem to reflect progression of various neurological conditions, including multiple sclerosis and neurodegenerative dementia disorders.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Several studies have shown elevated levels of NfL in the CSF of patients suffering from neurodegenerative conditions. [7][8][9] Further, CSF NfL levels seem to reflect progression of various neurological conditions, including multiple sclerosis and neurodegenerative dementia disorders. 10,11 Ultrasensitive methods have enabled the quantification of NfL in serum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation